Comparison of mechanical and bond properties of oil palm kernel shell concrete with normal weight concrete - Alengaram, Ubagaram Johnson; Mahmud, Hilmi; Jumaat, Mohd Zamin (Academic Journals, 2010)
The comparison of the fresh, mechanical and bond properties of grade 30 lightweight concrete, namely oil palm kernel shell concrete (OPKSC) with normal weight concrete (NWC) of similar strength is presented in this paper. Oil palm kernel shell (OPKS), an industrial waste has been used as lightweight aggregates (LWA) in the OPKSC. In addition, mineral admixtures, 10 of silica fume and 5 fly ash have been used. The OPKSC produced a density reduction of about 20 compared to NWC. The addition of silica fume enhanced the compressive strength and thus OPKSC produced 28-day compressive strength up to 37 MPa. The bond stress of the OPKSC was found about 86 of the corresponding NWC; however, there was no slip failure between OPKSC and the reinforcement. Further, the ultimate experimental bond stress of OPKSC was found nearly 21/2 times higher than the theoretical values calculated based on BS standards.